Faktor-Faktor yang Berhubungan dengan Kejadian Multi Drug Resistant Tuberculosis (Mdr-Tb) di RSUD Dr.H. Abdul Moeloek Provinsi Lampung - Restiana Cahyani; Umi Romayati Keswara; Rudi Winarno (Universitas Malahayati Lampung, 2025)
ABSTRACT Multidrug-resistant tuberculosis (MDR TB) is the resistance of Mycobacterium tuberculosis to several anti-tuberculosis drugs (OAT). Based on the data obtained during the initial data collection in the medical record sectionat the Regional General Hospital dr. H. Abdul Moeloek the number of inpatient visits to patients in 2022 (January-December) was recorded as many as 486 TB patients undergoing OAT sensitivity testing during the period stated. It is known that there is a relationship between these factors and the incidence of multidrug resistant tuberculosis (MDR-TB) at RSUD Abdul Moeloek Hospital, Lampung Province in 2023. Using a quantitative analytic design with a case control approach. The sample of this research is 140 cases and 140 controls. The sampling technique used purposivesampling technique. Data analysis used the chi-square statistical test. Based on the frequency distribution of respondents, in the case group a history of co-morbidities was 101 respondents (72.1%). It was known that thenutritional status in the case group was mostly in the thin category of 108 respondents (77.1%). the majority of caseswere in the category of repeat treatment cases, 96 respondents (68.6%). Shows that history of co-morbidities (p value 0.000. OR 7.209), nutritional status (p value 0.000. OR 4.772), history of previous treatment (p value 0.000. OR5.650). There is a relationship between a history of co-morbidities, nutritional status, and history of previoustreatment with the incidence of multidrug resistant tuberculosis (MDR-TB) at Abdul Moeloek Hospital, LampungProvince in 2023. Research advice is given to related parties to participate in prevention and transmission efforts MDRTB in Lampung Province. Keywords: MDR-TB Incidence, History of Co-Morbidities, Nutritional Status, History of Previous Treatment ABSTRAK Multidrug-resistant tuberculosis (MDR TB) adalah resistensi Mycobacterium tuberculosis terhadap beberapa obat anti-tuberkulosis (OAT). Berdasarkan data yang didapatkan pada saat pengambilan data awal di bagian rekam medis Rumah Sakit Umum Daerah dr. H. Abdul Moeloek jumlah kunjungan rawat inap pada pasien tahun 2022 (Januari-Desember) tercatat sebanyak 486 pasien tb menjalani pemeriksaan uji sensitivitas OAT pada periode yang telah disebutkan.Diketahui faktor- fator yang berhubungan dengan kejadian multidrug resistant tuberkulosis ( M D R - T B ) di RSUD Abdul Moeloek Provinsi Lampung tahun 2023. Menggunakan desain analitik kuantitatif dengan pendekatan casecontrol. Sampel penelitian ini adalah 140 kasus dan 140 kontrol. Teknik pengambilan sampel menggunakan teknikpurposive sampling. Analisis data menggunakan uji statistik chi-square. Berdasarkan distribusi frekuensi responden Pada kelompok kasus riwayat penyakit penyerta sebanyak 101 responden (72,1%),Diketahui status gizi pada kelompok kasus sebagian besar dengan kategori kurus sebanyak 108 responden (77,1%), Diketahui bahwa riwayat pengobatansebelumnya pasien TB pada kelompok kasus sebagian besar dengan kategori kasus pengobatan ulang sebanyak 96 responden (68,6%). Menunjukan bahwa riwayat penyakit penyerta (p value 0,000. OR 7,209), status gizi (p value 0,000. OR 4,772), riwayat pengobatan sebelumnya (p value 0,000. OR 5,650). Ada hubungan antara riwayat penyakitpenyerta, status gizi, dan riwayat pengobatan sebelumnya dengan kejadian dengan kejadian multidrug resistant tuberkulosis ( M D R - T B ) di Rsud Abdul Moeloek Provinsi Lampung tahun 2023. Saran penelitian diberikan kepadapihak-pihak terkait agar berpartisipasi dalam upaya pencegahan dan penularan TB MDR di Provinsi Lmpung. Kata Kunci : Kejadian MDR-TB, Riwayat Penyakit Penyerta, Status Gizi, Riwayat Pengobatan Sebelumnya Kata Kunci: Penyakit penyerta- Status Gizi- Riwayat Pengobatan-MDR-TB